USE OF MEDIA INDEX CARD MATCH IN ARABIC LANGUAGE LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES - Ade Arip Ardiansyah; Nanang Kosim; Dini Oktaviani (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to evaluate the effect of using Index Card Match learning media with cooperative learning methods on the learning outcomes of grade VIII-G students of Mts Negeri 3 Purwakarta on Arabic mufradāt material. This study used classroom action research methods. Learning outcome data was measured using 20 multiple-choice tests relevant to mufradāt material. The results of the analysis of this study show that the use of Index Card Match media with cooperative methods can improve student learning outcomes. This study concluded that students' learning outcomes before using Index Card Match media obtained an average pretest score of 54, while after using Index Card Match media, the average score on the posttest increased to 74.5. Follow-up studies may involve larger samples and different learning materials to better generalize these findings.